Hubungan Penggunaan Media Kartu Huruf Dengan Kemampuan Membaca Permulaan Siswa Kelas 1 SD - Sri Sabar (Universitas Sebelas Maret, 2022)
The problem that exists is that the teacher does not understand and is creative in choosing the learning media that will be used to stimulate the initial reading ability of the first graders of SD Negeri 3 Klepu Ceper Klaten Gunung Learning is still done by spelling and giving examples using the blackboard. The solution to overcome this problem is to use interesting media for students, one of which is using letter card media to introduce beginning reading for grade 1 students at SD Negeri 3 Klepu Ceper Klaten . In this study, reading is meant by students' ability to recognize letters, pronounce letter sounds, and pronounce letters clearly. This study aims to determine the relationship between the use of letter card media and the early reading ability of students in grade SD Negeri 3 Klepu Ceper Klaten.